Unveiling Zakat Decision: Exploring the Role of Religiosity, Moral Reasoning, Peer Influence, and System Fairness in Shaping Institutional Trust and Customer Zakat Intentions - Susilowati, Fitriah Dwi; Ridlwan, Ahmad Ajib; Yasin, Achmad; Monoarfa, Hilda; Shikur, Anwar Adem (ZISWAF, 2023)
Zakat is an Islam instrument used to help alleviate poverty and improve community welfare. Even though the potential of this instrument in Indonesia is very large, the income is still very low due to the lack of trust known as Muzakki (zakat payer). Therefore, this research aimed to explore the factors that influence Muzakki in zakat institutions and the provision intention. Data collected from a survey of 207 valid observations was validated using the partial least squares structural equation modeling (PLS-SEM) to examine the variables and examine the predictive relevance of the model. The results showed that peer influence and system fairness influence trust institutions, while zakat institution can improve fairness and transparency for Zakat recipients. Furthermore, to enhance the trust of Muzakki, marketers need to employ strategies to influence a group of individual to ensure customers are inclined to trust the zakat institution.